2020
DOI: 10.1029/2019wr025770
|View full text |Cite
|
Sign up to set email alerts
|

Coal Mining Impacts on Baseflow Detected Using Paired Catchments

Abstract: Large‐scale coal mining not only disturbs natural landscapes but also alters catchment hydrological processes. Although investigating how mining activities such as open cut and/or underground mining change catchment baseflow is critical for understanding mining‐related hydrological mechanisms and for helping water resource management, published data on these changes have not been well documented. This study uses data‐driven approaches to examine how baseflow changes in four sets of paired catchments in the Hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…The changes in soil properties induced from ground fissures mainly comes from the alteration in hydrogeological processes, which are influenced by multiple characteristics of ground fissures [22,23]. Some research has indicated that the width and density of ground fissures are significantly correlated with the change of soil moisture, cohesion, and organic matter [24], by determining the rate and direction of runoff around ground fissures [25].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in soil properties induced from ground fissures mainly comes from the alteration in hydrogeological processes, which are influenced by multiple characteristics of ground fissures [22,23]. Some research has indicated that the width and density of ground fissures are significantly correlated with the change of soil moisture, cohesion, and organic matter [24], by determining the rate and direction of runoff around ground fissures [25].…”
Section: Introductionmentioning
confidence: 99%
“…Coal mining activities can have severe and long-term impacts on catchment hydrological processes and stream ecosystems [23,24]. Relevant studies have shown that coal mining and drainage processes form goaf-like funnels (similar to pumping wells) around the coal mine, resulting in the decline of the surrounding groundwater level [25].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the changes of hydrological variables in the two basins, the impact of human activity on runoff is explored. The principle of this method is simple, but the test period is too long and the cost is high, so it is limited to small basin applications [16][17][18]. Therefore, according to the actual situation of the study area, the appropriate quantitative analysis method needs to be selected to ensure the accuracy of the study results.…”
Section: Introductionmentioning
confidence: 99%